2021
DOI: 10.1038/s41598-021-94575-w
|View full text |Cite
|
Sign up to set email alerts
|

AC conductivity and correlation effects in nano-granular Pt/C

Abstract: Nano-granular metals are materials that fall into the general class of granular electronic systems in which the interplay of electronic correlations, disorder and finite size effects can be studied. The charge transport in nano-granular metals is dominated by thermally-assisted, sequential and correlated tunneling over a temperature-dependent number of metallic grains. Here we study the frequency-dependent conductivity (AC conductivity) of nano-granular Platinum with Pt nano-grains embedded into amorphous carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…where T 0 is the characteristic temperature, ∼100 K for many GMs [84]. The decreases in GM conductivity at 75 K compared to 300 K indicate that ϕ c ∼ 0.4-0.5 for both Co-YSZ and Mo-YSZ.…”
Section: Electrical Transportmentioning
confidence: 99%
“…where T 0 is the characteristic temperature, ∼100 K for many GMs [84]. The decreases in GM conductivity at 75 K compared to 300 K indicate that ϕ c ∼ 0.4-0.5 for both Co-YSZ and Mo-YSZ.…”
Section: Electrical Transportmentioning
confidence: 99%
“…GMs have been studied for >50 years [12,13] for both fundamental and applied research in nanoelectronics [14], plasmonics [15], superconductivity [16], and magnetism [17]. While GMs with various metals have been investigated, nearly all GM studies employed oxide-based insulators, such as SiO 2 , Al 2 O 3 , or yttria-stabilized zirconia (YSZ), with notable non-oxides including MgF 2 [18], BN [19], and carbon-based [20,21] GMs. Recently, we found that GMs with non-noble metals and oxide insulators form metal-oxides, which deleteriously increase GM conductivity at j < j c [5].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Tunable frequency filters may cover multiple frequencies to meet different scenarios in multiple band operations.Nanogranular materials comprise disordered nanometer-sized granular metals dispersed in a host matrix and are a robust platform for studying complex disordered solids. [10,11] Based on this platform, a variety of intriguing phenomena have been discovered that involve the interplay of electronic, [12,13] magnetic, [14,15] optical, [16,17] and thermal properties, [18,19] as well as quantum [20] and superconductive behavior. [21] At diluted granular fractions (typically less than the percolation threshold of 50 vol%), the materials are in the dielectric regime, whereby both DC [22,23] and AC [24,25,26,27] electrical transport properties have been widely studied in this regime.…”
mentioning
confidence: 99%